The Fight Over Water Fluoridation in Israel-Potential Modesof Action in Light of the "American Experience" - Yuval Vered, DMD, MPH; Harold D. Sgan-Cohen, DMD, MPH (Blackwell Synergy, 2002)
The article "Why I continue to support water fluoridation" by Herschel S. Horowitz (1) published in 2000 was a reply to "Why I changed my mind about water fluoridation" by John Colquhoun (2) in 1997. These two papers are only small examples, along with many publications in the United States and other parts of the world, of the ongoing intensive, emotional, and relentless debate over water fluoridation. The controversy started even before 1945, when Grand Rapids, Michigan, became the first city to adjust the level of the fluoride in its drinking water to the recommended optimal level (3).